The World Ovarian Cancer Coalition Every Woman Study: Identifying Challenges and Opportunities to Improve Survival and Quality of Life. Issue 5 (May 2021) - Reid, Frances; Bhatla, Neerja; Oza, Amit M.; Blank, Stephanie V.; Cohen, Robin; Adams, Tracey; Benites, Amanda; Gardiner, Diane; Gregory, Sylvia; Suzuki, Makiko; Jones, Annwen
Abstract : (Abstracted from Int J Gynecol Cancer 2021;31:238–244) The prognosis for ovarian cancer remains poor even in highly developed countries such as the United States, with approximately 1 in 6 women dying within 3 months of diagnosis and 1 in 2 dying within 5 years. Given that the global incidence of ovarian cancer is set to rise 55% by 2035, urgent action is required to improve survival and quality of life in this patient population.